2007
DOI: 10.1007/bf03024859
|View full text |Cite
|
Sign up to set email alerts
|

The use of MSD model in credit scoring

Abstract: A credit scoring classification problem can be defined as a decision process in which information from application forms for new or extended credit is used to separate the applicants into good and bad credit risks. In the credit industry, it is important to find a method that optimally separates applicants into 'goods' and 'bads' as good classification models can provide competitive advantage. These classification models can be developed by statistical techniques (e.g. statistical discriminant analysis and log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…A major revision on this concept, its beginnings and the difficulties arising when developing accurate methods of scoring is made by Mester (1997). Credit scoring models are usually based on classification models rely on information from applicants to separate good and bad credit risks (Falangis, 2007;Shi and Xu, 2016). A closely related problem is loan optimization.…”
Section: Introductionmentioning
confidence: 99%
“…A major revision on this concept, its beginnings and the difficulties arising when developing accurate methods of scoring is made by Mester (1997). Credit scoring models are usually based on classification models rely on information from applicants to separate good and bad credit risks (Falangis, 2007;Shi and Xu, 2016). A closely related problem is loan optimization.…”
Section: Introductionmentioning
confidence: 99%
“…The above models do not take the issue that the distributions of customer data are often highly imbalanced into account in customer credit scoring. The so-called class imbalance means that the applicants with bad credit constitute only a very small minority of the data (usually 2% of the total customers) [10]. For example, the Council of Mortgage Lenders, UK, reported that in the second quarter of 2010, the number of mortgages three or more months in arrears, i.e., default applicants with bad credit stood at 2.17% of total outstanding mortgages [11].…”
Section: Introductionmentioning
confidence: 99%